Some peculiarities of implementation of departmental control over the intelligence activities - Nurtaev, A.B.; Shaimuhanov, A.D.; Manapov, K.B. (Opción, 2019)
The article presents a special study of the features of the implementation of departmental control over intelligence activities (IA) via a set of complementary research methods such as the theoretical and comparative method. As a result, the principle of democratic centralism is the combination of centralized leadership with the development of the creative initiative of local authorities. In conclusion, principle of timeliness, principle of adequacy, principle of completeness, principle of differentiation of responsibility, principle of democratic centralism, principle of planning should be applied in IA for the purpose of reaching the most working way of this sphere.